Earning Through Obsolescence. An Examination of Falling Household Durables Usage Lifespans in the United States 1970-2018 - Sean Dillon (Capital as Power - Toward a New Cosmology of Capitalism, 2025)
This study examines the declining usage lifespan of household consumer durables in the United States between 1970 and 2018, situating the phenomenon within a heterodox political economy framework. While mainstream economic narratives attribute the rising rate of consumer durable waste over this time to “overconsumption” driven by consumer materialism, this study challenges that perspective through an empirical analysis of waste generation, consumer spending, depreciation rates, and corporate profitability within the consumer durables sector. *** The findings reveal a significant divergence between rising levels of durable goods waste and relatively stable per capita `real' consumer spending, suggesting that falling product longevity is largely not demand-driven. Instead, the data indicates that manufacturers have profitably reduced product durability, as evidenced by increasing rates of geometric depreciation and a rise in total sectoral earnings without proportional increases in earnings margins. *** These findings align with the theory of “planned obsolescence,” whereby firms deliberately shorten product lifespans to drive replacement purchases and sustain profit growth. Given that this strategy cannot be adequately explained within conventional neoclassical economic models, the article draws the Veblenian theory of “strategic sabotage” to conceptualize the deliberate underutilization of technological capacity in pursuit of pecuniary gains. The study provides both empirical and theoretical evidence that the decline in consumer durables product longevity observed between 1970 and 2018 is structurally embedded in capitalist production of consumer durables goods.
Keywords: P1; Q53; 330; capital accumulation; obsolescence; overconsumption; sabotage; waste; United States